The Problem of “Nationalization” of the Elite as Confirmation of Theory of the “Best People” by J. Ortega y Gasset - Boyko, Sergey (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
Based on theory of the “Best People” by J. Ortega y Gasset the author made an attempt to investigate the role of upper stratum of society in modernization of the political regime on principles of democracy and polyarchy. The author shows the role in the State of apparatus of power and administrative authorities, comprising professionally and morally trained public officers, providing stable and independent functioning of state institutions. In 2012 social and political events started in Russia, named “the nationalization” of the elite in political science. The interests of high political and enterprise social groups are coordinated with the interests of the State and civil society. The comparative analysis of Spanish and Russian political elites influences and impact on political stability to provide independent social and economic development of their countries is made. The state sovereignty reflects the ability of independency governing and manager of high social groups, the national elite. The role of military-political elite as a body of legitimate force in the State welfare is underlined separately. Modern models of democratic political regimes are not the aim, but the instrument of achieving welfare of people and the State. The events in Russia confirm significance of scientific works of the great thinker J. Ortega y Gasset.